Bioremediation of polyaromatic hydrocarbons (PAHs) using rhizosphere technology - Bisht,Sandeep (2015)
The remediation of polluted sites has become a priority for society because of increase in quality of life standards and the awareness of environmental issues. Over the past few decades there has been avid interest in developing in situ strategies for remediation of environmental contaminants, because of the high economic cost of physicochemical strategies, the biological tools for remediation of these persistent pollutants is the better option. Major foci have been considered on persistent organic chemicals i.e.polyaromatic hydrocarbons (PAHs) due to their ubiquitous occurrence, recalcitrance, bioaccumulation potential and carcinogenic activity. Rhizoremediation, a specific type of phytoremediation that involves both plants and their associated rhizospheric microbes is the creative biotechnological approach that has been explored in this review. Moreover, in this review we showed the significance of rhizoremediation of PAHs from other bioremediation strategies i.e. natural attenuation, bioaugmentation and phytoremediation and also analyze certain environmental factor that may influence the rhizoremediation technique. Numerous bacterial species were reported to degrade variety of PAHs and most of them are isolated from contaminated soil, however few reports are available from non contaminated soil. Pseudomonas aeruginosa, Pseudomons fluoresens, Mycobacterium spp., Haemophilus spp., Rhodococcus spp., Paenibacillus spp. are some of the commonly studied PAH-degrading bacteria. Finally, exploring the molecular communication between plants and microbes, and exploiting this communication to achieve better results in the elimination of contaminants, is a fascinating area of research for future perspective.